High-resolution axial MR imaging of tibial stress injuries - Mammoto Takeo; Hirano Atsushi; Tomaru Yohei; Kono Mamoru; Tsukagoshi Yuta; Onishi Sinzo; Mamizuka Naotaka (BMC, 2012)
Abstract Purpose To evaluate the relative involvement of tibial stress injuries using high-resolution axial MR imaging and the correlation with MR and radiographic images. Methods A total of 33 patients with exercise-induced tibial pain were evaluated. All patients underwent radiograph and high-resolution axial MR imaging. Radiographs were taken at initial presentation and 4 weeks later. High-resolution MR axial images were obtained using a microscopy surface coil with 60 × 60 mm field of view on a 1.5T MR unit. All images were evaluated for abnormal signals of the periosteum, cortex and bone marrow. Results Nineteen patients showed no periosteal reaction at initial and follow-up radiographs. MR imaging showed abnormal signals in the periosteal tissue and partially abnormal signals in the bone marrow. In 7 patients, periosteal reaction was not seen at initial radiograph, but was detected at follow-up radiograph. MR imaging showed abnormal signals in the periosteal tissue and entire bone marrow. Abnormal signals in the cortex were found in 6 patients. The remaining 7 showed periosteal reactions at initial radiograph. MR imaging showed abnormal signals in the periosteal tissue in 6 patients. Abnormal signals were seen in the partial and entire bone marrow in 4 and 3 patients, respectively. Conclusions Bone marrow abnormalities in high-resolution axial MR imaging were related to periosteal reactions at follow-up radiograph. Bone marrow abnormalities might predict later periosteal reactions, suggesting shin splints or stress fractures. High-resolution axial MR imaging is useful in early discrimination of tibial stress injuries.